Multi-axial material constitutive model updating based online numerical simulation method for seismic performance evaluation of shear wall structures. (May 2023) - Xu, Guoshan; Jiang, Yutong; Yang, Ge; Ning, Xizhan; Yu, Tianyu
Abstract: As an important symbol of building industrialization, precast shear wall structures (PSWSs) were widely used. Hybrid testing can provide reliable technical supporting for the seismic performance evaluation of PSWSs as well as shear wall structures (SWSs). However, inaccurate numerical models of structures and/or incomplete boundary loading conditions on the specimens may lead to the distortion of hybrid test results. The hybrid test method based on model updating of multi-axial materials has never been studied and applied for precisely disclosing the seismic performance of SWSs. For solving these problems, one Multi-Axial Material Constitutive Model Updating based Online Numerical Simulation Method (MAMCMU-ONSM) is proposed for SWSs and based on which the seismic performance of one PSWS is evaluated in this study. In the proposed method, the layered shell element with the MAMCMU is utilized for refined simulating the SWSs; furthermore, the overall restoring forces of SWSs are calculated by the layered shell element with updated MAMCM parameters of the overall structure for solving the incomplete boundary conditions problem. Firstly, the theory of the MAMCMU-ONSM for SWSs is proposed, and the OpenSees-Matlab-Hytest test platform for the MAMCMU-ONSM is presented. Secondly, the layered shell element with the MAMCM as well as the corresponding UKF identification method are proposed for SWSs. Finally, the seismic performance of one PSWS is evaluated by the proposed method. It is shown that the proposed MAMCMU-ONSM is feasible for SWSs, and the OpenSees-Matlab-Hytest test platform exhibits excellent reliability. The numerical simulation results show that the relative errors are all less than 0.4362% and the overall average error is 0.2518%. The experimental results show that the identification error is about 8.2%. The numerical and experimental results prove the effectiveness and the accuracy of the proposed MAMCMU-ONSM and the advantage of the proposed MAMCMU-ONSM over the traditional hybrid method. The experimental results also indicate that the PSWS meets the requirements of corresponding seismic design code. The MAMCMU-ONSM provides economical and precise investigation strategy for SWSs and may have broad application prospects in the field of civil engineering.